2002
DOI: 10.1248/bpb.25.738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Osthole on Postmenopausal Osteoporosis Using Ovariectomized Rats; Comparison to the Effects of Estradiol.

Abstract: Osthole (7-methoxy-8[3-methylpent 2-enyl]coumarin), a plant coumarin compound, is extracted from a Chinese herb Cnidium monnieri (L.) CUSS which has been used since ancient times in China as a tonic and aphrodisiac. It was reported that castrated mouse received subcutaneous injections of an alcoholic extract of Cnidium monnieri (L.) CUSS once a day for 21 d, the copulation period appeared, 1) this suggests that this alcoholic extract (including osthole) may have the estrogen-related activities. It has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 18 publications
6
51
0
Order By: Relevance
“…OVX also causes a reduction in BMD, bending strength of the femur and compressive strength of the vertebral bodies. Our results concerning biochemical markers of bone turnover, bone strength and histomorphometry in the OVX rats are therefore consistent with published studies of this model [23][24][25][26][27][28][29][30]. Administration of SCH 57068 to the OVX-treated animals in our experiment appeared to markedly reduce the increase in overall bone turnover induced by OVX.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…OVX also causes a reduction in BMD, bending strength of the femur and compressive strength of the vertebral bodies. Our results concerning biochemical markers of bone turnover, bone strength and histomorphometry in the OVX rats are therefore consistent with published studies of this model [23][24][25][26][27][28][29][30]. Administration of SCH 57068 to the OVX-treated animals in our experiment appeared to markedly reduce the increase in overall bone turnover induced by OVX.…”
Section: Discussionsupporting
confidence: 92%
“…The OVX rat model mimics changes in bone metabolism observed in human postmenopausal osteoporosis. Biochemical markers of bone resorption and formation reflecting bone turnover are elevated after OVX and return to low levels after estrogen repletion or after treatment with antiresorptive agents [23][24][25][26]. OVX also causes a reduction in BMD, bending strength of the femur and compressive strength of the vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Osthole has been isolated from Prangos spp. (Abyshev & Denisenko, 1970;Kuznetsova et al, 1979b;Sajjadi et al, 2009) and has exerted many pharmacological effects like blood triglyceride and cholesterol lowering effects via suppression of HMG-CoA reductase gene expression (Ogawa et al, 2007), antispasmodic (Sadraei et al, 2012(Sadraei et al, , 2013, and anti-osteoporosis (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that osthole possesses antiproliferation, vasorelaxation, antihepatitis, anti-inflammatory, antiaggregatory, and antiallergic effects (Ko et al, 1992;Huang et al, 1996;Liu et al, 1998;Matsuda et al, 2002;Yang et al, 2003). Osthole has been shown to exhibit estrogen-like effects, preventing postmenopausal osteoporosis in ovariectomized rats (Li et al, 2002). It also has been reported to stimulate cell proliferation of osteoblast-like cells (Meng et al, 2004).…”
mentioning
confidence: 99%